Rumen microbes and some of their biotechnological applications - Abdullah, Norhani (2006)
The rumen is a unique ecosystem, well suited to maintain a dense population of microbes. Its anaerobic and reduced conditions are favourable for an intensive microbial degradation of feedstuffs consumed by the host. The rumen bacteria, protozoa and fungi produce the enzymes to hydrolyse the various nutrients present in the feed. The cellulases and hemicellulases degrade the complex plant cell wall polysaccharides and the products are assimilated and fermented by the microbes for their own energy requirement. The end-products of fermentation, mainly the volatile fatty acids and microbial protein are made available to the host. The massive amount of genetic materials and gene products present in the rumen offers a source of unlimited materials for the development of biosensors, bioassays and enzymes for biotechnological applications .